PENGEMBANGAN KURIKULUM MADRASAH IBTIDAIYAH NEGERI DALAM MENINGKATKAN MUTU PEMBELAJARAN - Gustina Gustina; Rosman Efendi; Kamel Kamel; Ismail Syakban (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze curriculum development at State Islamic Elementary Schools (Madrasah Ibtidaiyah Negeri) in improving the quality of learning. Methods: This research employed a qualitative descriptive approach with a case study design. Data were collected through observations, in-depth interviews with school principals and teachers, and documentation analysis related to curriculum planning and implementation. Data analysis was carried out through data reduction, data display, and conclusion drawing. Results: The findings indicate that curriculum development at Madrasah Ibtidaiyah Negeri has been implemented through planning, implementation, and evaluation stages, but it has not yet been carried out optimally. Constraints include limited teacher understanding of curriculum development, lack of managerial support, and inadequate learning facilities. Novelty: This study emphasizes the importance of managerial roles in curriculum development to systematically improve learning quality at Islamic elementary schools.